Evaluación de la extracción de pigmentos vegetales como la antocianina a partir de diferentes frutos silvestres para uso alimenticio (2021)
In this work a theoretical study of the extraction of colorants from wild fruits is carried out, for this an investigation of the Colombian and foreign regulations regarding these additives is carried out. In addition, a search for the best extraction methods is carried out, with microwave extraction being the method that gives the best performance. Subsequently, a search is developed for the optimal conditions in different foods in which it meets its applicability and finally, a design proposal is made for the extraction of colorant on an industrial scale, taking as raw material the agraz (wild fruit)